LHOKSEUMAWE SOCIETY RITUALS AT THE SOLAR ECLIPSE (Study of the Solar Eclipse March 9th 2016 and December 26th 2019) - Ismail Ismail (Al-Hilal: Journal of Islamic Astronomy, 2020)
This paper aims to determine the understanding and series of activities carried out by the Lhokseumawe City community during a solar eclipse that is classified as a religious ritual, with an anthropological approach, then get a picture of religiosity in the ritual carried out by the Lhokseumawe City community when a solar eclipse occurs. Referring to two samples of solar eclipse events in Lhokseumawe City, namely the eclipse of March 9, 2016, and December 26, 2019. the form of ritual performed by the people of Lhokseumawe City during the solar eclipse event is by visiting the location prepared by the committee and announced several days before the eclipse occurred which begins with remembrance and blessings in the congregation while waiting for another call. Then performs eclipse prayers in congregation, then eclipse sermons like holiday sermons. Some pilgrims believe that a solar eclipse is a sign of disaster and rituals are performed as a form of protection from that form of disaster. Some others believe it is a sign of God's power and rituals are performed as a form of gratitude and religious instruction.